The international hospitality business : management and operations - Yu, Lawrence (Haworth Hospitality Press, 1999)
International Hospitality Business: Management and Operations will introduce hospitality managers to the most up-to-date developments in hospitality to prepare you for the rapidly changing world of international hospitality. This book is a compilation of the most current research in global operations. It examines new developments, new management concepts, and new corporate mergers. International Hospitality Business analyzes and discusses the complexity of the political, economic, financial, commercial, and cultural environment within which international business takes place to help you become a productive global manager. Through International Hospitality Business, you will learn how an effective global hospitality manager must have a broad trans-disciplinary perspective that includes studies in politics, culture, and geography to better prepare for the complexity of international operations. Expand your knowledge of how to deal with the issues that confront hospitality firms and managers in international development and operations by: understanding the great demand for competent managers to oversee operations in foreign countries because of the explosive growth of the international hospitality industry exploring the complex issues faced by hospitality managers when they are assigned to work overseas gaining insight into international hospitality firms’policies regarding developmental strategy, organizational structure, marketing, finance, accounting, and human resource management recognizing the international hospitality industry as an integral part of the service import and export business to help students gain a better understanding of managerial roles With The International Hospitality Business, you will examine world travel patterns, major hotel chains, and foodservice companies in different regions of the world to expand your knowledge and help you face the dynamic changing world of international hospitality. While this volume provides you with important, comprehensive knowledge that will help you manage the your overseas hospitality operations in a way that keeps the most important person in any business--the customer--contented.
Keywords: International Cooperation; mezinárodní spolupráce; pohostinství (Non-MESH); management, organizace a řízení zdravotnictví